The phenomenon of estrangement and divergence between the political authority and scholars in the Islamic Maghreb (7-9 AH / 13-15 CE( - Bessedik, abdelkarim (The Algerian Historical Journal, 2026)
This article deals with the phenomenon of rupture between political authority and scholars in the Islamic Maghreb during the period from the middle of the seventh century to the ninth century AH (Q7-9 AH) after the collapse of the Almohad state and its impact on intellectual life, through three main elements: The reasons for the estrangement and the divergence between rulers and scholars In the society of the Islamic Maghreb, then the manifestations of estrangement and estrangement between rulers and scholars, and the tribulations that affected scholars of all kinds, such as murder, imprisonment, exile, alienation, dismissal from employment, etc., as well as the effect of the estrangement on the scientific movement and the society of the Islamic Maghreb, both positively and negatively. In this article, we try to address the issue of controversy over the relationship between rulers and scholars, so that the relationship between the scholarly elite and the political class represents an important issue in the history of the Islamic Maghreb, despite the consensus of opinions between political theorists and historians, and the need for some kind of integration between rulers and scholars. Far from collision and disharmony.